Combined use of hepatoprotective agents - S. V. Okovity (Лечащий Врач)
Despite all the polyetiological nature of liver damage, the similarity of the main links of pathogenesis allows us to use a fairly close pathogenetic therapy, one of the components of which can be hepatoprotective agents. Despite a large number of scientific studies and many years of clinical experience in the use of hepatoprotective agents, the boundaries of this pharmacological group use are still not clearly defined due to the fact that many of the clinical studies did not meet the modern principles of evidence-based medicine.The results of studying the chemical structure, pharmacodynamics and pharmacokinetics, the practical use of hepatoprotective agents do not give unambiguous answers to many questions regarding the indications for their use, the choice of a specific drug, regimens and duration of treatment.To a large extent, this also applies to the combined use of hepatoprotective agents, the validity and feasibility of which is not always obvious. Questions about how rational the combination of hepatoprotectors can be, whether it gives any clinical benefit, and whether such tactics are a step toward unjustified polypharmacy, remain without a clear answer.The clinical and experimental studies verviews conducted over the past decades has allowed us to identify several combinations that have the most pronounced effect on the morphological changes in the liver, or mutually potentiate one of the pharmacological effects.